DNA origami devices for molecular-scale precision measurements. (8th December 2017) - Castro, Carlos E.; Dietz, Hendrik; Högberg, Björn
Abstract: Abstract : Structural DNA nanotechnology offers the capacity to construct ultraminiaturized devices with programmed nanoscale geometry, mechanical and dynamic properties, and site-specific molecular functionalities. These features and the possibility to position and orient molecules in user-defined ways may be exploited to create custom instruments for precision measurements of molecular-scale structure, dynamics, and interactions. Such devices may help constrain molecular motion along interesting reaction coordinates and may also exert forces to probe the mechanical properties or dynamics of molecules under study. Multiple ways of reading out device states may be used, including atomic force microscopy or transmission electron microscopy imaging, single-molecule or bulk fluorescence, or ionic conductivity as in nanopore systems. Early successes with custom scientific instruments based on DNA origami underline the tremendous potential to enable new approaches to making scientific discoveries in biological and synthetic materials systems.